2022
DOI: 10.1080/20008066.2022.2104007
|View full text |Cite
|
Sign up to set email alerts
|

Encountering children and child soldiers during military deployments: the impact and implications for moral injury

Abstract: Background: During a deployment, soldiers must make seemingly impossible decisions, including having to engage with child soldiers. Such moral conflicts may continue to affect service members and veterans in the aftermath of a deployment, sometimes leading to severe moral distress, anguish, and personal crises. Service providers have increasingly argued that as a diagnosis, Post-Traumatic Stress Disorder (PTSD) cannot account for these deeply personal and painful moral conflicts. In light of this, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…related to mission framework, deployment environment, occupational impacts, and formal supports), often eliciting moral conflicts, challenges in decision-making, and intense reactions such as shock, mistrust, and anger. These findings are consistent with previous reviews and editorials (Denov, 2022 ; Ein et al, 2022 , 2023 ), emphasizing training and policy gaps which leave personnel inadequately prepared to manage the tactical and psychological implications of deployment-related encounters with children. Of note, such implications may also be legal and political, and serve to exacerbate consequences to soldiers and to children.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…related to mission framework, deployment environment, occupational impacts, and formal supports), often eliciting moral conflicts, challenges in decision-making, and intense reactions such as shock, mistrust, and anger. These findings are consistent with previous reviews and editorials (Denov, 2022 ; Ein et al, 2022 , 2023 ), emphasizing training and policy gaps which leave personnel inadequately prepared to manage the tactical and psychological implications of deployment-related encounters with children. Of note, such implications may also be legal and political, and serve to exacerbate consequences to soldiers and to children.…”
Section: Discussionsupporting
confidence: 91%
“…Importantly, deployment-related encounters with children have been characterized as potentially morally injurious events (PMIEs) (Denov, 2022 ; Ein et al, 2023 ), defined as experiences that deeply transgress a person’s deeply held moral beliefs leading to distress and impairment (Litz et al, 2009 ). Epidemiological research on stressful deployment experiences in the context of the Canadian mission to Afghanistan reveals high exposure to PMIEs, with 58% of returning soldiers endorsing exposure to at least one type of PMIE, and 43% reporting experiences where they were unable to help women and children who were suffering (Nazarov et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] International deployments increasingly involve exposure to complexities less common in previous conflict eras, including engagement with unmarked enemy combatants, suicide bombings, and encounters with children. Importantly, while deployment-related encounters with children have been shown to be associated with mental health and other consequences in military personnel, [3] and have been conceptualized as potentially morally injurious events (PMIEs; i.e., events that can lead to mental health impacts due to a violation of moral beliefs or values) [4,5], the effects of such encounters remain largely understudied. For example, approximately 58% of the 33,500 Canadian military personnel deployed in NATO operations in Afghanistan experienced PMIEs, with 43% of these individuals endorsing having experienced PMIEs involving women and children.…”
Section: Canadian Armed Forces Veterans' Perspectives On the Effects ...mentioning
confidence: 99%
“…[5,16] As such, military personnel are increasingly at risk for serious psychological sequelae due to exposure to these situations, which in many ways are representative of prevailing conceptualizations of PMIEs. [4,5,16] Consequences of PMIE exposure are serious, as research has demonstrated consistent associations with PTSD, depression, anxiety, and most concerningly suicidality. [1,9] Furthermore, studies have shown that exposure to and direct involvement in PMIEs is associated with PTSD symptom severity, even after controlling for exposure to combat (e.g., receiving enemy fire, going on patrols), [17,18] showcasing that distinct qualities of deployment events can have particular impacts on mental health.…”
Section: Mental Health and Military Deploymentsmentioning
confidence: 99%
See 1 more Smart Citation